RESPONSABILIDAD SOCIAL EMPRESARIAL Y EL ECOSISTEMA - Begazo Villanueva, José (2012)
Environmental responsibility of an organization must be understood as an ethical commitment, taken from the direction, and that can be implemented by different instruments, depending on the degree of organizational commitment to the preservation of its natural environment and the means at their disposal to meet their environmental goals. Every organization must be aware of the environmental impact generated, and drastically reduce the need in the shortest time possible, to promote sustainable development. To this end, the present research has proposed the development of a theoretical framework for better understanding of the subject studied, emphasizing what Peruvian companies are doing for the environment and the ecosystems that are the backbone of our future sustainability of our rich biodiversity and second to expose cases of three flagship institutions of our country. It concludes with the contributions that the study believes should be considered in any CSR policy and specifically in environmental responsibility.